Formal Reconciliation to Adjudge Psychological and Physical Abuses Committed During Civil War in Acehnese Society - Zulfan (Indian Journal of Forensic Medicine & Toxicology, 2021)
The civil war caused many psychological and physical trauma for common people. As a way to end this suchwar, related parties usually take formal and social measures in peace agreement. In this case, the formationof the truth and reconciliation commission (TRC) in Aceh is one of a task to accomplish after the signingof memorandum of understanding in Helsinki (MoU Helsinki), and the implementation of law number11, 2006 on the Acehnese government. On one side, the situation has urged TRC to be formed in Aceh,however local regulation has not specifically organized the forming of the commission. Reconciliation inAceh comes with its own character by stressing more on the application of religious, custom, and localwisdom approaches without forgetting the effort of truth revealing on some cases of heavy human rightsviolation which occurred during conflict. The Acehnese society is a society who lives with their Islamicvalues and specific custom.